Flat-rate tax systems and their effect on labor markets - Andreas Peichl (IZA World of Labor, 2014)
The potential economic outcomes resulting from a flat rate of income tax have been the subject of an ongoing academic and political debate. Many observers have suggested that the introduction of a flat tax would be beneficial for a country's economy, having a positive influence on the labor market and the gross domestic product by enhancing incentives to work, save, invest, and take risks. A flat tax also significantly simplifies income taxation which increases tax compliance and reduces tax planning, avoidance, and evasion. However, despite flat taxes being on the political agenda in many countries, in practice their implementation has mostly been restricted to the transition economy countries of Eastern Europe. There is no one single flat tax system in place in these countries though; one rate does not fit all.
Keywords: F22; F63; I3; J3; J61; 330; flat tax; employment; simplification; labor supply; microsimulation